2017
DOI: 10.3390/su9071191
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Model Based on Cooperative Relationship in Sustainable Construction Projects

Abstract: Considering the cooperative relationship between owners and contractors in sustainable construction projects, as well as the synergistic effects created by cooperative behaviors, a cooperative incentive model was developed using game theory. The model was formulated and analyzed under both non-moral hazard and moral hazard situations. Then, a numerical simulation and example were proposed to verify the conclusions derived from the model. The results showed that the synergistic effect increases the input intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 61 publications
(80 reference statements)
0
23
1
Order By: Relevance
“…The project benefits will almost certainly be reduced if both the owner and contractor tend to maximize and prioritize their own benefits [17,65]. Therefore, the optimal behavioral arrangements of these two parties are to achieve their own maximum benefits, but under the strict condition of maximizing the project benefit.…”
Section: Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…The project benefits will almost certainly be reduced if both the owner and contractor tend to maximize and prioritize their own benefits [17,65]. Therefore, the optimal behavioral arrangements of these two parties are to achieve their own maximum benefits, but under the strict condition of maximizing the project benefit.…”
Section: Hypothesismentioning
confidence: 99%
“…where A is the outcome coefficient of the effort levels of the contractor, which can manifest by the integrated technical level and comprehensive management ability of the contractor [17]. The outcome coefficient of the effort levels is related to the operational management capability, project experiences and employee competences of the contractor.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Game theory is divided into cooperative game theory and non-cooperative game theory [47]. This paper deals with the problem of hybrid power system planning in EI, which can reach an alliance in advance, so it belongs to the category of cooperative game and emphasizes on collective rationality.…”
Section: Cooperative Game Theorymentioning
confidence: 99%
“…Jiang, et al [17] investigated the influence of transformational leadership on employee performance in sustainable construction projects, and found that employee sustainable performance was positively influenced by transformational leadership and more than half of that influence was mediated by their organizational citizenship behavior. Wu, et al [18] developed a cooperative incentive model to investigate the cooperative relationship between owners and contractors in sustainable construction projects, as well as the synergistic effects created by cooperative behaviors. Mella and Pellicelli [19] investigated the levers that weaken people's intention of conducting sustainable behaviors.…”
mentioning
confidence: 99%